Successful percutaneous mitral valve leaflet repair for primary mitral regurgitation results in functional improvement and positive cardiac reverse remodelling. (13th July 2021) - Craven, TP; Chew, PG; Gorecka, M; Brown, LAE; Das, A; Chowdhary, A; Jex, N; Thirunavukarasu, S; Dall"armellina, E; Levelt, E; Schlosshan, D; Malkin, C; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Percutaneous mitral valve leaflet repair can be an effective treatment for primary mitral regurgitation (MR) patients deemed high-risk for surgery. Accurate assessment of cardiac reverse remodelling is essential to optimise future patient selection. Cardiovascular magnetic resonance (CMR) is the reference standard for cardiac volumetric assessment and compared to transthoracic echocardiography (TTE) provides superior reproducibility in MR quantification. Prior CMR studies have analysed cardiac reverse remodelling following percutaneous intervention in combined cohorts of primary and secondary MR patients. However, as aetiology of MR can significantly impact outcomes, focused studies are warranted. Purpose: Assess cardiac reverse remodelling and quantify changes in MR following percutaneous mitral valve leaflet repair for primary MR using the reference standard (CMR). Methods: 12 patients with at least moderate-severe MR on TTE were prospectively recruited to undergo CMR imaging and 6-minute walk tests (6MWT) at baseline and 6 months following percutaneous mitral valve leaflet repair (MitraClip). CMR protocol involved: left-ventricular (LV) short axis cines (bSSFP, SENSE-2, 10mm, no gap), transaxial right-ventricular (RV) cines (bSSFP, SENSE-2, 8mm, no gap), two and four chamber cines and aortic through-plane phase contrast imaging, planned at the sino-tubular junction. MR was quantified indirectly using LV and aortic stroke volumes. Results: 12 patients underwent percutaneous mitral valve leaflet repair (MitraClip) for posterior mitral valve leaflet prolapse, however 1 patient declined follow up after single-leaflet clip detachment resulting in 11 patients (age 83 ± 5years, 9 male) completing follow up imaging. At 6-months: significant improvements occurred in New York Heart Association functional class (Table 1) and 6MWT distances (223 ± 71m to 281 ± 65m, p = 0.005) and significant reductions occurred in indexed left ventricular end-diastolic volumes (LVEDVi) (118 ± 21ml/m2 to 94 ± 27ml/m2, p = 0.001), indexed left ventricular end-systolic volumes (58 ± 19ml/m2 to 48 ± 21ml/m2, p = 0.007) and quantitated MR volume (55 ± 22ml to 24 ± 12ml, p = 0.003) and MR fraction (49 ± 9.4% to 29 ± 14%, p= <0.001). There were no statistically significant changes in left ventricular ejection fraction (LVEF), right ventricular dimensions/ejection fraction or bi-atrial dimensions (Table 1). All patients demonstrated decreased LVEDVi and quantified MR (Figure 1). Conclusion: Successful percutaneous mitral valve leaflet repair for primary MR results in reduction in MR, positive LV reverse remodelling, preservation of LVEF, and functional improvements. Larger CMR studies are now required to further guide optimal patient selection.